2014
DOI: 10.1016/j.tecto.2014.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic significance of porosity and permeability regimes in the red beds formations of the South Georgia Rift Basin

Abstract: A simple, new porosity/permeability-depth profile was developed from available laboratory measurements on Triassic sedimentary red beds (sandstone) from parts of the South Georgia Rift (SGR) basin in order to investigate the feasibility for long-term CO2 storage. The study locations were: Sumter, Berkeley, Dunbarton, Clubhouse Crossroad-3 (CC-3) and Norris Lightsey wells.As expected, both porosity and permeability show changes with depth at the regional scale that was much greater than at local scale. The sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…These results suggest finer‐grained lacustrine strata may have superior reservoir properties to the coarse‐grained fluvial sandstones due to better sorting, and that in the Newark basin, reservoir properties of the finer‐grained lacustrine formations should also be evaluated. Furthermore, a separate study focused on tectonic regimes in the SGR basin suggested that those high porosity‐permeability lacustrine samples came from a structural block with distinctly different tectonic history, potentially separated from the rest of the basin by a system of faults [ Akintunde et al ., ]. Intrabasin faults are also common in the Newark Basin, especially in the central and southern parts [e.g., Schlische , ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest finer‐grained lacustrine strata may have superior reservoir properties to the coarse‐grained fluvial sandstones due to better sorting, and that in the Newark basin, reservoir properties of the finer‐grained lacustrine formations should also be evaluated. Furthermore, a separate study focused on tectonic regimes in the SGR basin suggested that those high porosity‐permeability lacustrine samples came from a structural block with distinctly different tectonic history, potentially separated from the rest of the basin by a system of faults [ Akintunde et al ., ]. Intrabasin faults are also common in the Newark Basin, especially in the central and southern parts [e.g., Schlische , ].…”
Section: Discussionmentioning
confidence: 99%
“…In the South Georgia Rift (SGR), another rift basin on the eastern North American margin evaluated for its CO 2 storage potential, laboratory analysis of porosity and permeably on about a dozen core plugs and sidewall cores is available [Akintunde et al, 2014[Akintunde et al, , 2013. The data suggest that coarse fluvial sandstones have medium to low matrix porosity (2-15%) and low permeability (10 23 210 21 mD), attributed to poor sorting, high angularity and small pore throats [Akintunde et al, 2013].…”
Section: 1002/2015gc006240mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to connectivity, other materials properties are important in this quest, for example, the porosity of a medium, defined as the volume fraction of its voids (Thakur 2017). Porosity affects permeability so strongly (Akintunde et al 2014;Akinlotan 2016) that Archie proposed a porosity-permeability relationship, derived for sandstones, limestones and muddy sands, which predicts a tenfold increase in permeability when porosity increases by merely 3% (Archie 1950). Because it has been suggested that porosity intrinsically depends on the microstructure of porous materials (Shen et al 2018), we performed a sensitivity analysis on the effect of macro-and microporosity on permeability (Apostolopoulou et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of red-bed soft rock containing weak interlayers can be studied by laboratory and field analyses of the mineralogical composition of the weak interlayer [24,25]. Structural features such as faults, joints, interlayer slippage zones, and pelletization dissection are usually well developed and are considered to be other types of main structure plane in red beds, such as the interlayer slippage zone (a structurally related feature) of red beds located in southwestern China [26] and faults or fractures at the depth of red beds in the South Georgia Rift (SGR) basin [27]. It is well known that rock mass structures play a dominant role in the stability of a rock mass [11,16,28].…”
Section: Introductionmentioning
confidence: 99%